Analisis Berita Acara Pemeriksaan (BAP) Pasal 338 KUHP Jenis “Pembunuhan Biasa”: Studi Kasus Tindak Pidana Penganiayaan yang Mengakibatkan Kematian di Kelurahan Nunu, Kecamatan Tatangga, Kota Palu - Finsesius Samara; Mariano Junior Rawu Ravim; Irene Roswitha Eugenia Mooy; Apriani Imelda Mau; Johanes Malvino Bethan; Louis Agung Towa Tance; Christian Jordan Pareira; Yustinus De Carlos Ghari Tao (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This article analyzes the criminal offense of assault resulting in death based on a case study in Palu City. The article employs a normative legal research method with a case study approach, supported by secondary data in the form of investigation reports, witness statement, and physical evidence. The results show that the perpetrator’s physical kaviolence against the victim’s vital body parts caused a causal relationship with the death. Juridically, the act fulfills the elements of a criminal offense as regulated in Article 338 of the Indonesian Criminal Code and Article 351 paragraph (3). This study emphasizes the importance of accuracy in offense qualification in cases of assault resulting in the loss of human life.